Scarce fire activity in north and north-western Amazonian forests during the last 10, 000 years. (4th July 2021) - Gosling, William D.; Maezumi, S. Yoshi; Heijink, Britte M.; Nascimento, Majoi N.; Raczka, Marco F.; van der Sande, Masha T.; Bush, Mark B.; McMichael, Crystal N.H.
ABSTRACT: Background: Fire is known to affect forest biodiversity, carbon storage, and public health today; however, comparable fire histories from across forest regions in Amazonia are lacking. Consequently, the degree to which past fires could have preconditioned modern forest resilience to fire remains unknown. Aim: We characterised the long-term (multi-millennial) fire history of forests in Amazonia to determine spatial and temporal differences in fire regimes. Methods: We collated and standardised all available charcoal data extracted from continuously deposited lake sediments (n = 31) to reconstruct a ca. 10, 000-year fire history for: (i) north and north-western, (ii) south-western, and (iii) eastern parts of Amazonia. Results: Charcoal was found across Amazonia, but it was less abundant in the north and north-western regions. Regionally distinct periods of elevated charcoal deposition were identified at between ca. 4000 and 1500 (eastern), 3000–1000 (south-western) and 2500–2000 (north and north-western) years ago. Conclusions: Forests in eastern and south-western Amazonia have been exposed to fire activity over recent millennia, while the forests in north and north-western Amazonia have grown under conditions largely free of fire activity. Consequently, we hypothesise that the forests in eastern and south-western Amazonia are preconditioned to be relatively more resilient to the threat of increased modern fire activity.